2021
DOI: 10.2147/rmhp.s288003
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Health-Care Workers’ Unwillingness to Continue Working During the Peak of COVID-19 in Western Ethiopia: An Extended Parallel-Process Model Study

Abstract: Willingness to work in disasters is context-specific and corresponds to the nature, magnitude, and threats posed by a particular public health emergency. None us is certain that our health professionals will continue to provide service should the COVID-19 pandemic crisis climb to its worst level. It was with this uncertainty in mind that this study was done to assess predictors of the unwillingness of health-care workers (HCWs) to continue providing their professional services during the climax of the COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Healthcare workers are facing an increasing threat as a result of confronting COVID-19 pandemic. 26 COVID-19 has become one of the major causes of death, which has still continued to claim the lives of healthcare professionals worldwide 27 most of whom are forced to work under circumstances where there are acute shortages of personal protective materials. 28 The innovation of vaccination, no doubt, would help to maintain public health and safety 1–4 if the necessary activities of recipients’ level of awareness is raised in a way they become not hesitant to receive the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare workers are facing an increasing threat as a result of confronting COVID-19 pandemic. 26 COVID-19 has become one of the major causes of death, which has still continued to claim the lives of healthcare professionals worldwide 27 most of whom are forced to work under circumstances where there are acute shortages of personal protective materials. 28 The innovation of vaccination, no doubt, would help to maintain public health and safety 1–4 if the necessary activities of recipients’ level of awareness is raised in a way they become not hesitant to receive the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicate that healthcare workers across the world are facing an increasing threat as a result of confronting severe and contagious diseases, including COVID-19. 1 , 2 Furthermore, the COVID-19 pandemic has remained one of the leading causes of death which claimed the lives of many well-trained and experienced healthcare professionals, especially in Europe. 3 Many healthcare workers have died after contracting the virus while treating the patients infected by COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…3,5 It is indicated that healthcare workers are facing an increasing threat as a result of confronting severe and contagious diseases, including COVID-19. 6 Furthermore, the COVID-19 pandemic remains a major cause of death which has claimed the lives of many well trained and experienced healthcare professionals, especially in Europe. 7 Many healthcare workers have died after contracting the virus while treating patients infected by COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] The Coronavirus pandemic has also resulted in healthcare workers facing shortages of personal protective materials against COVID-19. 13 Woyessa et al 6 found that healthcare workers in Western Ethiopia are generally unwilling to continue working under circumstances where the spread of COVID-19 pandemic reached at its peak. According to the Health and Safety Authority, 10 safety and health guidelines are applicable to all workers in all settings, but the extent to which they are effectively implemented relies on many factors, including the adequacy of its facilities.…”
Section: Introductionmentioning
confidence: 99%